The Role of Phonological, Auditory Sensory and Cognitive Skills on Word Reading Acquisition: A Cross-Linguistic Study - Murphy, Cristina Ferraz Borges; Schochat, Eliane; Bamiou, Doris-Eva (Frontiers in Psychology, 2020)
Despite considerable evidence regarding the influence of orthography on reading processing, the impact of orthographic depth on reading predictors remains unclear. In addition, it also remains unknown the role of the orthography in the influence of auditory temporal processing and attention skills on word reading skills. The current study investigates the word reading predictors in a group of British and Brazilian children with typical development considering phonological, auditory sensory, short-term memory, and sustained attention skills. Rhyme and Alliteration skills predicted word reading in both groups; however, the correlation in the British group was more robust. Short-term memory was also correlated with reading in both groups; however, it was a significant word reading predictor only in the British group. The auditory sensory was not directly correlated with word reading in either group; however, it was involved with Rhyme and Alliteration performance only in the British group. Those results were discussed considering the complexity of the phonological structure and opaque orthography in English when compared to Portuguese, which indicates that the less transparent the orthography, the higher the importance of factors such as phonological awareness, short-term memory, and to some extent, auditory sensory processing skills on word reading acquisition. Those results emphasize the need to consider orthography and phonological features of a particular language when developing a reading assessment and treatments.